Reproductive Behaviour and Semen Characteristics of Exotic Rams under Temperate Conditions of Kashmir - ISLAM, R; KHAN, M Z; WANI, G M; GANAIE, T A S (The Indian Journal of Animal Reproduction, 2023)
Rams with sound reproductive health were selected from Corriedale, Polled Dorset and Hampshire breeds at University Sheep Research Station, Shuhama, Srinagar. Sexual behaviour like sniffing, kicking with fore legs, moving tongue in and out, courting grunt, Flehmen response, number of mounts required per collection and reaction time to I st mount were studied. Semen was collected with artificial vagina (AV) • using non-estrous ewe as dummy. The ejaculate was examined visually for volume, colour and consistency. Microscopic examination of semen was done for mass activity (0 t, 4 scales), initial motility Percentage, spermatozoa concentration, live sperm count and percent intact acro!<ome. The study was conducted during the a_utumn breeding season after the flock returned from high land pasture. Immediately after collection, keeping aliquots for spermatozoa concentration, the rest of the ejaculates were diluted with warm (30 °C) Egg Yolk Citrate Extender at the rate of I :2 for conducting other semen evaluation procedures. Comting grunt was only observed in Polled Dorset rams. Corriedale rams did. not show flehmen response. Sniffing, kicking with fore legs, moving tongue in and out were the common courtship pattern observed in all the breeds. Moving tongue in and out and reaction time to first mount were significantly (p<0.05) lower in Corriedale rams than Polled Dorset and Hampshire rams. Number of mounts required per collection, reaction time to first mount, ejaculate volume (ml), mass activity, sperm concentration (million/ ml), percent initial motility, percent live sperm and percent intact acrosome did not vary significantly among the breeds studied. Corriedale rams produced higher ejactilate volume, mass activity and sperm concentration than the other two breeds. However, the differences were r,on significant. It is revealed from the study that rams of all three breeds have potential for breeding; however, Corriedal ram is comparatively better under temperate agro-climatic conditions of Kashmir. Immediate dilution of the ejaculate with warm egg yolk citrate extender was beneficial in maintaining the sperm viability till fmther evaluation and processing of the ejaculate during low environmental temperatures.